2015
DOI: 10.1007/s10578-015-0617-0
|View full text |Cite
|
Sign up to set email alerts
|

The Prospective Links Between Hyperactive/Impulsive, Inattentive, and Oppositional-Defiant Behaviors in Childhood and Antisocial Behavior in Adolescence: The Moderating Influence of Gender and the Parent–Child Relationship Quality

Abstract: We prospectively investigated the effect of child hyperactive/impulsive, inattentive, and oppositional/defiant behaviors on the development of youth antisocial behaviors, and the moderating influence of gender and the parent-child relationship quality in a normative sample. Participants (N = 673, 50 % girls) were assessed at 10 years of age (parent reports) and at age 15 (parent and adolescent reports). Using latent change models, we found that initial levels of, as well as increases in, hyperactivity/impulsiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
8
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(14 citation statements)
references
References 57 publications
6
8
0
Order By: Relevance
“…These results are consistent with studies that have found trait impulsivity to be strongly related to ASBs (e.g. DeMarte, 2008, Thibodeau, Cicchetti, Rogosch, 2015Giannotta & Rydell, 2015). One alternative interpretation may be that the impulsive nonconformity and ASB constructs overlap.…”
Section: Discussionsupporting
confidence: 91%
“…These results are consistent with studies that have found trait impulsivity to be strongly related to ASBs (e.g. DeMarte, 2008, Thibodeau, Cicchetti, Rogosch, 2015Giannotta & Rydell, 2015). One alternative interpretation may be that the impulsive nonconformity and ASB constructs overlap.…”
Section: Discussionsupporting
confidence: 91%
“…These findings are consistent with evidence of the aggravating effects of negative parent-child interactions on youth development (e.g., Deault, 2010;McLeod et al, 2007) especially in early and middle adolescence (e.g. Giannotta & Rydell, 2016). Taken together, our results hint at different effects of maternal involvement and conflicted relationships, the first affecting internalizing problems/depressive mood in late adolescence and the other increasing externalizing types of problem behaviors in early-middle adolescence.…”
Section: Discussionsupporting
confidence: 91%
“…This may also apply to children showing hyperactive and inattentive symptoms. We found, in a previous study, that child hyperactive symptoms predicted youth antisocial behaviors only in children for whom the quality of the parent-child relationship had deteriorated from childhood to adolescence (Giannotta & Rydell, 2016). To our knowledge, the possible moderating role of the parent-child relationship in the association between child ADHD and youth depressive symptoms has not been investigated.…”
mentioning
confidence: 68%
“…Regarding hyperactivity behavior, this is also considered a predictor of future aggressive and violent behavior (Shaw & Gilliam, 2017), being associated more with boys than girls (Giannotta & Rydell, 2016).…”
Section: Discussionmentioning
confidence: 99%